Clinical Predictors of Pacing Device Implantation in Implantable Cardiac Monitor Recipients for Unexplained Syncope - Reina Tonegawa-Kuji, MD, PhD; Yuko Y. Inoue, MD, PhD; Michikazu Nakai, PhD; Koshiro Kanaoka, MD, PhD; Yoko Sumita; Yuichiro Miyazaki, MD; Akinori Wakamiya, MD, PhD; Keiko Shimamoto, MD, PhD; Nobuhiko Ueda, MD, PhD; Kenzaburo Nakajima, MD, PhD; Naoya Kataoka, MD, PhD; Mitsuru Wada, MD; et al. (CJC Open, 2023)
Background: Implantable cardiac monitors (ICMs) help investigate the cause of unexplained syncope, but the probability and predictors of needing a pacing device thereafter remain unclear. Methods: We retrospectively analyzed the data of patients who received ICM insertion for unexplained syncope with suspected arrhythmic etiology. The data were obtained from a nationwide database obtained between April 1, 2012 and March 31, 2020. Multivariable mixed-effects survival analysis was performed to identify predictors of pacing device implantation (PDI), and a risk score model was developed accordingly. Results: In total, 2905 patients (age: 72 years [range: 60-78]) implanted with ICMs to investigate the cause of syncope were analyzed. During the median follow-up period of 128 days (range: 68–209) days, 473 patients (16%) underwent PDI. Older age, history of atrial fibrillation, bundle branch block (BBB), and diabetes were independent predictors of PDI in multivariable analysis. A risk score model was developed with scores ranging from 0 to 32 points. When patients with the lowest quartile score (0–13 points) were used as a reference, those with higher quartiles had a higher risk of PDI (second quartile: 14–15 points, hazard ratio [HR]: 3.86, 95% confidence interval [CI]: 2.62–5.68; third quartile: 16–18 points, HR: 4.67, 95% CI: 3.14–6.94; fourth quartile: 19–32 points, HR: 6.59, 95% CI: 4.47–9.71). Conclusions: The 4 identified predictors are easily assessed during the initial evaluation of patients with syncope. They may help identify patients with a higher risk of requiring permanent PDI. Résumé: Contexte: Les moniteurs cardiaques implantables (MCI) aident à déterminer la cause d’une syncope inexpliquée, mais la probabilité et les facteurs prédictifs du besoin d’un dispositif de stimulation cardiaque par la suite demeurent incertains. Méthodologie: Nous avons analysé de façon rétrospective les données de patients s’étant fait implanter un MCI après une syncope inexpliquée et chez lesquels une étiologie d’arythmie était soupçonnée. Les données proviennent d’une base de données nationale et s’étendent du 1er avril 2012 au 31 mars 2020. Une analyse de survie multivariable à effets mixtes a été effectuée pour cibler les facteurs prédictifs de l’implantation d’un dispositif de stimulation cardiaque (IDSC), et un modèle de score de risque a été conçu en conséquence. Résultats: Au total, les cas de 2905 patients (âge : 72 ans [écart interquartile (ÉI) : 60-78]) ayant reçu un MCI pour déterminer la cause de la syncope ont été analysés. Durant la période de suivi médiane de 128 jours (ÉI : 68-209), 473 patients (16 %) ont subi une IDSC. L’âge avancé, les antécédents de fibrillation auriculaire, le bloc de branche et le diabète étaient des facteurs prédictifs indépendants de l’IDSC dans l’analyse multivariable. Un modèle de score de risque a été conçu, les scores allant de 0 à 32 points. Lorsque les patients ayant un score dans le quartile inférieur (0 à 13 points) étaient utilisés à titre de référence, ceux ayant un score dans les quartiles supérieurs avaient un risque plus élevé d’IDSC (deuxième quartile : 14-15 points, rapport des risques instantanés [RRI] : 3,86, intervalle de confiance [IC] à 95 % de 2,62 à 5,68; troisième quartile : 16-18 points, RRI : 4,67, IC à 95 % de 3,14 à 6,94; quatrième quartile : 19-32 points, RRI : 6,59, IC à 95 % de 4,47 à 9,71). Conclusions: Les quatre facteurs prédictifs ciblés sont faciles à évaluer durant l’évaluation initiale des patients ayant subi une syncope. Ils peuvent aider à repérer les patients présentant un risque plus élevé d’avoir besoin d’un dispositif de stimulation cardiaque permanent.